Flight - Tong, Isabella Risselle (2019)
Flight is a one-person stage play about a girl overcoming her fear caused by a past traumatic experience on an airplane.The film is inspired by a personal experience and explores the fear and anxiety of boarding an airplane again using metaphorical representations of fear/anxiety (a fire dragon) and calmness/relaxation (a water dragon). Flight is a 2D animated short film done in TVPaint.